Commodity booms and racial inequality in Brazil - Bergamaschi, Gabriel Mendes (2024)
This dissertation analyzes the effect of commodity booms on the racial composition of Brazilian municipalities between 1872 and 1950, using panel data. To address the possibility of simultaneity between export revenues and migration, we use a time-varying and municipality-specific measure of potential export revenues, called the CAIP variable, which is calculated from a weighted average of each commodity\'s international price. Our results show that an increase of one standard deviation of potential exports in the recent past leads to an increase in the share of whites and a decrease in the share of blacks and mixed-race in the municipality. This effect is stronger in regions that cultivate sugar, cotton, and cocoa, and weaker in regions that cultivate coffee and tobacco. Our primary hypothesis is that we captured the decline of the sugar and cotton economy at the end of the 19th century, leading to a reallocation of workers to regions that cultivate coffee and tobacco crops. However, the transportation costs meant that only the wealthier white population could migrate, while the black and mixed-race population remained in areas where export revenues were lower.